Efficacy of Tamsulosin plus Tadalafil versus Tamsulosin as Medical Expulsive Therapy for Lower Ureteric Stones: A Randomized Controlled Trial - Gnyawali, Diwas (Adv Urol, 2020)
INTRODUCTION: Urolithiasis is one of the common disorder with which about 1/5(th) is found in the ureter, of which 2/3(rd) is seen in the lower ureter. Medical expulsive therapy is one of the routine modalities of treatment which uses various drugs acting on the ureter smooth muscle by different mechanism. We aim to compare the efficacy of combination vs. single drug. METHODS: This randomized controlled trial was done in 176 consecutive patients over a period of six months (March 2019 to August 2019) in Department of Urology and Kidney Transplant Surgery, Tribhuvan University Teaching. Participants were divided into two groups (Group A, tamsulosin plus tadalafil, and Group B, tamsulosin) from computer-generated random numbers. Therapy was continued for a maximum of 3 weeks. Stone expulsion rate, time to stone expulsion, analgesic use, number of colic and emergency room visits for pain, early intervention, and adverse effects of drugs were recorded. RESULTS: Among 176 patients who were enrolled in study, 7 were lost to follow-up, and 5 people required immediate intervention. There was a significant higher stone passage rate in group A than group B (64 vs. 50; P=0.025) and shorter expulsion time (1.66 vs. 2.32 weeks P=0.001) and less number of emergency room visits and colic episodes. No significant side effects were noted during study. CONCLUSION: Tamsulosin plus Tadalafil is more effective than tamsulosin with early passage of stone and decreased number of colic episodes and emergency visits without significant side effects for lower ureteric calculi of 5 mm to 10 mm.